Physicochemical properties of dietary protein as predictors for digestibility or releasing percentage of amino acids in monogastrics under in-vitro conditions - Yuan Zhao; Yaru Zhu; Guixin Qin; Li Pan; Hui Sun; Nan Bao; Mostafa Mohamed Hasham; Mohammed Hamdy Farouk (Italian Journal of Animal Science, 2022)
The nutritional values of the protein are related to its amino acid content, and its physicochemical properties. We aimed to determine the relationship between the variation of protein digestibility or the releasing coefficient of amino acids with the physicochemical properties of different feedstuffs. We analysed the secondary protein structure and solubility of 10 protein-rich feed ingredients, including soybean, soybean meal, dehulled soybean meal, fermented soybean meal, distiller’s dried grains with solubles (DDGS), feather meal, fish meal, rapeseed meal, corn gluten meal, and corn germ meal. The results showed that the soybeans and their products had greater protein solubility than the other dietary protein (p < .001). Fish meal, rapeseed meal and all soybean sources had the higher protein digestibility and releasing coefficient of amino acids, also reached different peaks in shorter times. But corn germ meal, corn gluten meal, and feather meal exhibited lower releasing coefficient of amino acids and weaker solubility (p < .001). The in-vitro protein digestibility or releasing coefficient of total amino acid had positive regression coefficients with α-helix, α-helix/β-sheet, and solubility; and a negative regression coefficient with β-sheet. Feedstuffs with faster amino acid releasing rate had higher α-helix, α-helix/β-sheet and solubility and lower β-sheet. Therefore, the physicochemical properties of the dietary protein could be used as predictors for the amino acids’ digestibility and amino acid bioavailability.Highlights We evaluated the protein solubility, protein digestibility, and releasing coefficient of amino acids among the most common feedstuffs for monogastric animals The physicochemical properties of dietary protein could be used as predictors for the digestibility or releasing rate of amino acids in monogastric. The feed industry formulation might be reconsidered since the most common feedstuffs possess novel concepts.